STRATEGI DAN INOVASI PENGEMBANGAN DIGITALISASI UMKM DI DESA KEDUNGSEGOG. - Jamal; Ian, Muhammad Rezki; Wahyudiono (JURNAL INOVASI HASIL PENGABDIAN (JIHAN), 2025)
Kedungsegog Village is an area that has local economic potential based on the agricultural, handicraft and trade sectors. Even though MSMEs in this village play an important role in creating jobs and increasing income, the results of observations show that MSMEs in Kedungsegog Village still have difficulty accessing adequate technology, apart from that, MSMEs do not have sufficient skills in utilizing digital technology for marketing and business management. , as well as product development. The implementation method for this service activity is carried out in 4 activity stages, namely agenda preparation and preparation of activity documents, socialization, technical assistance and evaluation of activity results. Overall, this activity succeeded in having a significant positive impact on the development of MSMEs in Kedungsegog Village, both in terms of mastery of digital technology, product innovation, increasing business efficiency and market expansion. Apart from that, collaboration between MSME players and various stakeholders also strengthens the digital business ecosystem in this village, encouraging more inclusive and sustainable local economic growth.